Digital Financial Literacy and Risk Perception: Its Impact on Personal Financial Management with Self-Control as a Mediating Variable in the Community in Binjai City - Sri Puji Lestari; Alfin Kusuma (International Journal Of Economics Social And Technology, 2026)
The rapid development of financial technology and the increasing prevalence of digital financial services have created both opportunities and challenges for household financial management. At the same time, rising consumptive behavior and easy access to digital transactions require individuals, particularly housewives as household financial managers, to possess adequate financial competencies and self-regulation abilities. This study aims to examine the influence of digital financial literacy and risk perception on personal financial management, with self-control serving as a mediating variable among housewives in Bhakti Karya Village, Binjai City. A quantitative approach with an associative research design was employed. The study involved 292 respondents selected using the Slovin formula through a proportionate sampling technique. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 3 software. SEM-PLS was chosen because of its ability to simultaneously test complex relationships among latent variables and mediation effects. The findings reveal that digital financial literacy has a positive and significant effect on both personal financial management and self-control. Risk perception positively and significantly affects self-control but does not directly influence personal financial management. This result indicates that awareness of financial risks alone is insufficient to improve financial management behavior unless it is supported by an individual's capacity for self-control. Furthermore, self-control positively and significantly affects personal financial management and successfully mediates the relationships between digital financial literacy, risk perception, and personal financial management. The study contributes to the behavioral finance literature by highlighting the central role of self-control as a psychological mechanism that transforms financial knowledge and risk awareness into effective financial management practices. These findings provide practical implications for policymakers and financial educators in designing programs that integrate digital financial literacy enhancement with self-control development to improve household financial well-being.